2017
DOI: 10.3390/ma10111249
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Contact Sensing and Characterizing of Mechanical and Dynamic Heat Transfer Properties of Porous Polymeric Materials

Abstract: Porous polymeric materials, such as textile fabrics, are elastic and widely used in our daily life for garment and household products. The mechanical and dynamic heat transfer properties of porous polymeric materials, which describe the sensations during the contact process between porous polymeric materials and parts of the human body, such as the hand, primarily influence comfort sensations and aesthetic qualities of clothing. A multi-sensory measurement system and a new method were proposed to simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A series of research works and methods developed based on the KES system have been reported, with some focusing on combining objective and subjective evaluations to obtain a regression model to predict fabric handle [ 10 ], some focusing on the measurement of certain mechanical properties such as bending rigidity and the relationship analysis between KES and FAST system [ 11 ], and some paying attention to automatic test process control [ 12 ]. Unlike the KES and FAST systems, which use several instruments, newly developed systems have been able to measure and evaluate the handle properties in one instrument [ 13 , 14 , 15 ], with the typical representative being the PhabrOmeter system developed by Pan [ 14 ]. The PhabrOmeter system applied the pattern recognition technique to evaluate handle properties and assess some visual attributes such as drape and wrinkle recovery, but the measured parameters and the test results did not have physical meanings.…”
Section: Introductionmentioning
confidence: 99%
“…A series of research works and methods developed based on the KES system have been reported, with some focusing on combining objective and subjective evaluations to obtain a regression model to predict fabric handle [ 10 ], some focusing on the measurement of certain mechanical properties such as bending rigidity and the relationship analysis between KES and FAST system [ 11 ], and some paying attention to automatic test process control [ 12 ]. Unlike the KES and FAST systems, which use several instruments, newly developed systems have been able to measure and evaluate the handle properties in one instrument [ 13 , 14 , 15 ], with the typical representative being the PhabrOmeter system developed by Pan [ 14 ]. The PhabrOmeter system applied the pattern recognition technique to evaluate handle properties and assess some visual attributes such as drape and wrinkle recovery, but the measured parameters and the test results did not have physical meanings.…”
Section: Introductionmentioning
confidence: 99%